Estudo da apneia do sono em pacientes obesos em programação de cirurgia bariátrica - Lopes Neto, Jose Mauricio [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Obstructive sleep apnea (OSA) is characterized by repetitive partial or complete upper airway collapse during sleep leading to sleep fragmentation, hypoxemia, hypercapnia, intrathoracic pressure oscillations and increased sympathetic activity. Obesity is the main risk factor for the development of OSA in adults as well as its most important reversible risk factor. The exact pathophysiology of OSA in obese patients remains poorly understood. Such narrow relationship between OSA and obesity can be observed in numbers, so nearly 40–45% of obese patients have OSA whereas 70% of patients with OSA are obese. Between 71–91% of the morbidly obese (BMI ≥ 40 kg/m2) present OSA. The purpose of this study was to evaluate the frequency and classify the severity of OSA in obese patients scheduled for bariatric surgery, also evaluating the risk for OSA pointed out by Berlin Questionnaire (BQ), excessive daytime sleepiness that was measured by Epworth Sleepiness Scale (ESS) and if one or both questionnaires would be tools for screening in such population. Patients (over 18 yrs) from the Outpatient Bariatric Surgery at Gastro-surgery Department were included. On the other hand, users of sedative medication, patients with oxygen-dependent lung disease or decompensated and/or congestive decompensated heart failure, presence of signs and/or other sleep disorders (narcolepsy, restless legs syndrome, insomnia), craniofacial deformities, diagnosis and/or previous OSA treatment were excluded. This group was submitted to anamnesis and specific physical examination and answered BQ and ESS. From such group, 35 patients were submitted to portable monitoring for OSA research and Stardust II (Respironics, Inc., USA) was used. The demographic data were described in their average and standard deviation as well as absolute number or percentage and compared for gender. BQ and ESS results were compared according to gender and BMI, being described in absolute numbers ...

A apneia obstrutiva do sono (AOS) é caracterizada pelo colabamento parcial ou completo, repetido das vias aéreas superiores durante o período de sono que leva a uma fragmentação do sono, hipoxemia, hipercapnia, oscilações da pressão intratorácica e aumento da atividade simpática. No adulto, a obesidade é o principal fator de risco para o desenvolvimento de AOS e o fator de risco reversível mais importante da AOS. A exata fisiopatologia da AOS em pacientes obesos permanece pouco compreendida. Essa estreita relação entre AOS e obesidade é constatada nos números, onde aproximadamente 40%-45% dos obesos têm AOS e 70% dos pacientes com AOS são obesos. Entre 71-91% dos obesos mórbidos (IMC ≥ 40 kg/m²) possuem AOS. O objetivo deste trabalho foi avaliar a frequência e classificar a gravidade da AOS em pacientes obesos em programação de cirurgia bariátrica. Além de avaliar a chance de AOS apontada pelo Questionário de Berlin (QB), a sonolência diurna excessiva através da Escala de Sonolência de Epworth (ESE) e se um ou ambos os questionários seriam instrumentos de screening nesta população. Foram incluídos pacientes do ambulatório de cirurgia bariátrica do serviço de gastrocirurgia com idade superior a 18 anos. Foram excluídos do estudo: usuários de medicamentos sedativos, portadores de doença pulmonar dependente de oxigênio ou descompensada e/ou insuficiência cardíaca congestiva descompensada, presença de sinais e/ou sintomas de outros distúrbios do sono (narcolepsia, síndrome das pernas inquietas, insônia), portadores de deformidades craniofaciais, diagnóstico e/ou tratamento de AOS previamente. Esse mesmo grupo foi submetido à anamnese e exame físico específico e respondeu ao QB e a ESE. Do grupo citado, 35 pacientes foram submetidos à poligrafia noturna para pesquisa de AOS. O aparelho utilizado foi o Stardust II (Respironics, Inc.,USA). Os dados demográficos foram descritos em suas médias e ...
Keywords: Sindrome da apneia do sono; Obesidade; Cirurgia bariátrica; Obesity Surgery